2017
DOI: 10.1038/bjc.2017.317
|View full text |Cite|
|
Sign up to set email alerts
|

Camptothecin suppresses NRF2–ARE activity and sensitises hepatocellular carcinoma cells to anticancer drugs

Abstract: Background:Resistance to chemotherapy is a major obstacle in the treatment of human hepatocellular carcinoma (HCC). Despite playing an important role in chemoprevention, nuclear factor erythroid 2-related factor 2 (NRF2) also contributes to chemo- and radio-resistance. The current study focusses on camptothecin as a novel NRF2 inhibitor to sensitise HCC to chemotherapy.Methods:The expression and transcriptional activity of NRF2 in human HCC biopsies and camptothecin-treated culture cells were determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 71 publications
(77 reference statements)
1
66
0
Order By: Relevance
“…These results indicate that cotreatment in A375 inhibits/AKT signaling while inhibiting Nrf2 expression. Similar results were obtained with camptothecin as another potential inhibitor of Nrf2 (data not shown) [ 45 , 46 ].…”
Section: Resultssupporting
confidence: 86%
“…These results indicate that cotreatment in A375 inhibits/AKT signaling while inhibiting Nrf2 expression. Similar results were obtained with camptothecin as another potential inhibitor of Nrf2 (data not shown) [ 45 , 46 ].…”
Section: Resultssupporting
confidence: 86%
“…Additionally, resveratrol, apigenin, luteolin and menadione have been demonstrated to display good therapeutic effects in animal models (45,(78)(79)(80). Camptothecin, chrysin and MS-275 have only been studied in vivo or in cell experiments, but may have potential to treat HCC (81)(82)(83). Other small molecular compounds have not yet been demonstrated to have effectiveness against HCC, and therefore further research is required.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou and colleagues demonstrated that Nrf2 expression increased when the BEL-7402 cell line was exposed to the 5-Fluorouracil, suggesting an involvement of this transcription factor in HCC chemoresistance [ 160 ]. The use of Camptotechin, a Nrf2 inhibitor, enhanced the sensitivity of HCC cell lines to chemotherapeutic agents, impairing cancer cell viability [ 161 ]. Furthermore, inhibition of Nrf2 through Apigenin reversed the drug-resistant phenotype.…”
Section: Nrf2 As a Mediator Of Resistancementioning
confidence: 99%
“…However, Halofuginone, similar to Brusatol, is not a specific Nrf2 inhibitor as it represses global protein synthesis, thus rapidly depleting Nrf2. Camptotechin, another alkaloid isolated from the Chinese tree Camptotheca acuminate, inhibits Nrf2 activity in HCC cells, reverting chemoresistance [ 161 ]. However, its mechanism of action is not clear, as no direct effect in promoting Nrf2 protein degradation could be provided.…”
Section: Nrf2 As a Molecular Targetmentioning
confidence: 99%